IMPLEMENTATION OF SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY (SETS) IN NATURAL SCIENCE LEARNING BASED ON ISLAMIC VALUES IN ELEMENTARY SCHOOLS - Din Azwar Uswatun; Iis Nurasiah; Rohmat Widiyanto; Fauzan Fauzan; Tri Suryaningish (JMIE (Journal of Madrasah Ibtidaiyah Education), 2025)
This study aims to examine the urgency and implementation of the Science, Environment, Technology, and Society (SETS) approach in elementary science education through the integration of Islamic values as a foundational framework. The research seeks to address common challenges in science learning, such as students’ low science process skills, limited scientific literacy, and weak environmental awareness. The study employed a qualitative descriptive design with an analytical orientation. Data were collected through classroom observations, document analysis, and semi-structured interviews involving teachers and students from elementary schools implementing SETS-based learning. Data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing to ensure analytical rigor, credibility, and validity. The results reveal that integrating Islamic values within the SETS framework enhances students’ conceptual understanding of science, science process skills, and literacy. It also strengthens students’ environmental awareness, scientific reasoning, and positive attitudes toward learning. The SETS model creates meaningful connections between science, technology, environment, and society, aligned with Islamic principles. The findings imply that SETS-based learning integrated with Islamic values can serve as a transformative pedagogical model to improve the quality of elementary science education by nurturing students’ scientific competence, environmental ethics, and spiritual awareness as integral components of holistic education.